Analysis of Freelancer Income at the Millennial Job Center (MJC) as the Competence Development Program of the East Java Super Corridor (EJSC) in East Java - Nurwanti, Nida Azhari; Satria, Dias (Journal of Development Economic and Social Studies, 2025)
The creative economy contributed IDR 1.53 trillion to the Gross Domestic Product (GDP) in 2024, employing approximately 26.5 million people. However, the average monthly income of freelancers in East Java remained low at IDR 1.4 million in 2024, significantly below the provincial minimum wage (UMP) of IDR 2.1 million (BPS, 2025). This indicates a gap between the potential and the reality of the digital labor market. This study aims to analyze the influence of competence, social capital, market conditions, job characteristics, and digital technology on income variation among freelancers in the Millennial Job Center (MJC) program. A quantitative approach using ordinal logistic regression was applied, based on responses from 288 MJC freelancers across five administrative regions (Bakorwil) in East Java. The analysis reveals that competence and market conditions have a positive and significant effect on freelancer income, while social capital, job characteristics, and technology utilization do not show a significant impact. These findings highlight the importance of strengthening competence and improving freelancer competitiveness through training, cross-sector collaboration, and government policy support.